Efl Pre-Service Teacher Practicing Instructional Language During the Micro-Teaching Practicum - Nadya Dita Shaliha (Fakultas Ilmu Budaya, 2025)
Micro-teaching is a method used to prepare pre-service teachers for the real classroom. Another way to define micro-teaching is as a teaching method particularly utilized in pre-service teacher education to train pre-service teachers methodically by letting them practice key teaching techniques (Uzun, 2012). Allen & Ryan (1969) in Arsal (2014) also stated that micro-teaching is real teaching where the typical classroom complications are simplified so that pre-service teachers can concentrate on developing particular skills and self‐efficacy to improve practice. Speaking is one of the most prominent language skills that pre-service teachers will utilize in their professional lives. It is classified as an appealing talent that demands individuals to be unique and creative and to develop themselves in order to communicate (Aktay, 2021). In addition to general speaking skills, one of the most important speaking skills for pre-service teachers to develop is the competence to deliver instruction to the students. Effective instruction depends heavily on teachers' ability to communicate during microteaching. Instructional language is used to teach academic subjects in educational contexts (Pflepsen 2019, p.26). According to Kyeyune (2010) and Marie (2013), it is considered that instructional language assists in learning and makes subject matter easier to understand. It has a significant global impact on education, and the context, curriculum, teacher preparation, and student participation affect its effectiveness. Instructional language can be an international language like English, the nation's official or national language, the student's mother tongue, or a combination of these (Peyton, 2015). This observational was conducted to explore how EFL pre-service teachers practice instructional language during the micro-teaching practicum. This research was undertaken at one of the universities in Indonesia. Participants in this study were pre-service teachers from one of the universities in Indonesia. There was a criterion determined to select participants in this study. The criterion was a pre-service teacher with no teaching English experience. The fact that three pre-service teachers took micro-teaching classes, had no prior teaching experience, and it was their first time practicing instructional language should be taken into account when selecting them. The data result of this research was analyzed using thematic analysis. Based on the result. pre-service teachers were seen to applied five out of eight teaching skill that were the focus of micro-teaching practicum. These skills are opening and closing class, questioning, explaining materials, reinforcement, and managing class. Other than that, pre-service teachers also were seen to face difficulty in practicing instructional language. Pre-service teachers were observed to have difficulty in speaking English while practicing instructional language during the micro-teaching practicum that was indicated by code switching and stuttering.
Reupload file repository 19 Februari 2026_Ratna
Keywords: Efl Pre-Service Teacher Practicing Instructional Language